Breast Milk Is a Potential Reservoir for Livestock-Associated Staphylococcus aureus and Community-Associated Staphylococcus aureus in Shanghai, China - Li, Xiaoliang; Zhou, Yun; Zhan, Xianlin; Huang, Weichun; Wang, Xing (Frontiers in Microbiology, 2018)
Breast milk is the first choice in feeding newborn infants and provides multiple benefits for their growth and development. Staphylococcus aureus usually exists in breast milk and is considered one of the most important causative infective agents. To be effective in preventing and controlling S. aureus infections among infants, the aim of this study was to determine the occurrence and molecular characteristics of S. aureus isolated from 1102 samples of breast milk between 2015 and 2016 in Shanghai, China. Out of 71 S. aureus strains isolated, 15(21.1%,15/71) were MRSA and all the strains were characterized by spa typing, Multi-Locus Sequence Typing, SCCmec typing, antibiotic resistance testing and virulence-associated genes. A total of 18 distinct sequence types (STs) and 36 spa types were identified within the 71 isolates, among which the most frequently represented was ST398 (19.7%, 14/71), followed by ST7 (18.3%, 13/71), ST59 (16.9%, 12/71). The three predominant STs accounted for more than one half of all S. aureus isolates. The most prevalent spa types were t091(12.7%,9/71), followed by t571(8.5%,6/71), t189(7.0%,5/71), t034(5.6%,4/71), t437(5.6%,4/71) and t701(4.2%,3/71). All MRSA isolates belonged to SCCmec IV and V, accounting for 66.7% and 33.3% respectively. Notably, 23 (32.4%) S. aureus strains were multidrug resistance (MDR), including 4 (5.6%) MRSA and 19 (26.8%) MSSA strains, and MDR isolates were mostly resistant to penicillin, erythromycin and clindamycin. All isolates exhibited simultaneous carriage of at least 5 of 33 possible virulence genes and the most prevalent genes detected were icaA(100%), clfA(100%), hla (100%), sdrC(94.4%), hlg2(88.7%), lukE(57.8%). 39(54.9%, 39/71) isolates, including 9 (12.7%) of MRSA isolates, harbored ≥10 tested virulence genes evaluated in this study. The pvl gene was detected in 8 strains, which represented 5 different STs, with ST59 being the most one. Overall, our findings showed that S aureus strains isolated from breast milk were mainly MSSA (78.9%, 56/71) and exhibited high genetic diversity in Shanghai area of China. Breast milk was a reservoir for LA-SA (ST398) and CA-SA (ST59),which was likely a vehicle for transmission of multidrug-resistant S.aureus and MRSA lineages. This is a potential public health risk and highlights the need for good hygiene